Territorial Economic and Ecological Systems and Methods of Their Management - Raxmonazarov Paxlovon Yigitaliyevich; Tuychiyeva Odina Nabiyevna (American Journal of Economics and Business Management, 2024)
Sustainable development from an ecological point of view presupposes the sustainability of the biological and physical system. At the same time, the main attention is paid to ensuring the adaptation of ecological systems to changes. The use of natural resources, environmental pollution and the loss of biological species deprive ecological systems of the possibility of self-healing. Based on this, this article contains the necessary proposals for the sustainable development of the functioning of economic and environmental systems and improving their management efficiency.